Growth and distribution pattern of the world manufacturing output : a statistical profile - Andreoni, Antonio (UNIDO ViennaAT, 2014)
Analyses manufacturing trends over the last two decades for nearly 200 countries. Documents the three most relevant stylised facts that characterise the last two decades, viz., positive relatiionship linking manufacturing value added per capita and gross domestic product per capita for different; the process of redistribution of manufacturing value added across different countries and a set of country groups over the period under consideration; and finally particular emphasis which is given to the two most striking facts underlying the transformation of the current manufacturing landscape. Presents estimates of the manufacturing loss by country groups and statistics on the different country performances.